‘We Make Ourselves at Home Wherever We are’ – Older People’s Placemaking in Newton Hall - van Hoven, Bettina; Douma, Linden (European Spatial Research and Policy, 2012)
The aim of this paper is to explore older in-migrants’ experiences and perceptions of their spatial context at the neighbourhood level, the key aspects in their attachment to the neighbourhood, and the role of place in their experience of ageing. Our qualitative research was carried out in Newton Hall (United Kingdom). The findings show that older people can have a proactive role in terms of placemaking and their own wellbeing. However, the study also reveals that the condition of the spatial context can either support or hinder older people’s sense of wellbeing.